To complete the input-output table for the function \( f(x) = (x - 2)^2 + 3 \), we will calculate the output (f(x)) for various input values (x).
Let's choose some input values (for example, x = 0, 1, 2, 3, 4) and calculate the corresponding outputs.
-
For \( x = 0 \): \[ f(0) = (0 - 2)^2 + 3 = (2)^2 + 3 = 4 + 3 = 7 \]
-
For \( x = 1 \): \[ f(1) = (1 - 2)^2 + 3 = (-1)^2 + 3 = 1 + 3 = 4 \]
-
For \( x = 2 \): \[ f(2) = (2 - 2)^2 + 3 = (0)^2 + 3 = 0 + 3 = 3 \]
-
For \( x = 3 \): \[ f(3) = (3 - 2)^2 + 3 = (1)^2 + 3 = 1 + 3 = 4 \]
-
For \( x = 4 \): \[ f(4) = (4 - 2)^2 + 3 = (2)^2 + 3 = 4 + 3 = 7 \]
Now we can summarize the results in an input-output table format:
| Input (x) | Output (f(x)) | |-----------|---------------| | 0 | 7 | | 1 | 4 | | 2 | 3 | | 3 | 4 | | 4 | 7 |
You can now drag and drop the outputs 7, 4, 3, 4, and 7 into the corresponding response areas in your table based on the inputs you've selected.